2020
DOI: 10.1186/s12864-020-07272-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of long non-coding RNAs related to grain yield in foxtail millet [Setaria italica (L.) P. Beauv.]

Abstract: Background Long noncoding RNAs (lncRNAs) have been reported to play critical roles in diverse growth and development processes in plants. However, the systematic identification and characterization of lncRNAs in foxtail millet is nearly blank. Results In this study, we performed high-throughput sequencing of young spikelets from four foxtail millet varieties in different yield levels at booting stage. As a result, a total of 12,378 novel lncRNAs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Its production and research have been neglected, perhaps partly due to its poor yield ( Sagar et al, 2020 ). Therefore, improving millet yield and resilience to stress is an urgent issue ( Zhao et al, 2020 ). Foxtail millet productivity and production in the semi-arid region of Rayalaseema, India, faces immense challenges of drought and heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Its production and research have been neglected, perhaps partly due to its poor yield ( Sagar et al, 2020 ). Therefore, improving millet yield and resilience to stress is an urgent issue ( Zhao et al, 2020 ). Foxtail millet productivity and production in the semi-arid region of Rayalaseema, India, faces immense challenges of drought and heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although the phenotype and expression of genes controlling grain size and weight are altered in RNA interference plants, the accurate regulation mechanisms remain to be further studied. One reasonable speculation derived from studies of Setaria italica and chickpea is that lncRNAs related to grain yield act as miRNA target mimics and regulate expression of targets by competing for the interaction between miRNAs and their target mRNAs [36,37] (Figure 1). In fact, a few years ago, researchers demonstrated that the role of a rice lncRNA acts as an endogenous miRNA target mimic (eTM), in which osa-eTM160 attenuated the repression of osa-miR160 on osa-ARF18 mRNAs during early anther developmental stages, thereby affecting rice seed set and seed size [38].…”
Section: Embryogenesis and Endosperm Developmentmentioning
confidence: 99%
“…Further, it has been shown that the unsaturated fatty acids are responsible for forming volatiles, thus leading to an unpleasant aroma during germination in foxtail millet ( Li et al, 2021b ). A recent study identified 18 long non-coding RNAs (lncRNAs) in relation to grain yield and predicted them to function as miRNA target mimics ( Zhao et al, 2020 ). The nutritional quality of foxtail millet was analyzed in response to elevated CO 2 levels and found that e CO 2 significantly enhanced the accumulation of K, Mn, Zn, and starch and promoted P accumulation.…”
Section: Omics Resources In Setariamentioning
confidence: 99%